The Statistics of Equatorial Spread-F and Effects on Critical Frequency at Chumphon, Thailand - Phimmasone Thammavongsy; Pornchai Supnithi; Watid Phakphisut; Kornyanat Hozumi; Takuya Tsugawa; Kallaya Bannop (My University, 2020)
This work presents the study of equatorial spread-F (ESF) characteristics based on the occurrence percentages and durations during the maximum solar activity of the 24 th solar cycle at Chumphon station (CPN), Thailand.The statistics of ionogram data covering all months in 2014 are obtained from the ionosonde station.The effects of ESFs on communication signals are denoted by comparing the critical frequency of F2 layer (foF2) with ESFs.The results show the high ESF occurrence percentages in the equinoctial months and some months during the solstices.
Keywords: Geophysics and Gravity Measurements